How can we better engage female athletes? A novel approach to health and performance education in adolescent athletes - Roche, M.; McIntyre, A.; Oliver, C.; Sainani, K.; Boyd, T.; Stoner, A.; Kraus, E. (BMJ Open Sport & Exercise Medicine, 2024)
Objectives To evaluate the impact of a video series versus online pamphlets/blog posts on Female Athlete Triad (Triad) and Relative Energy Deficiency in Sport (REDs) knowledge in high school female runners.